2011
DOI: 10.1007/s00423-011-0874-8
|View full text |Cite
|
Sign up to set email alerts
|

Current practice and future perspectives in the treatment of short bowel syndrome in children—a systematic review

Abstract: The treatment of SBS patients remains very complex. It is eminent to find the best therapeutic option for each patient and to individualize and modify the different possible types of applied techniques frequently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 73 publications
0
18
0
11
Order By: Relevance
“…These procedures pertain to autologous methods of intestinal reconstruction and could be categorized further into two subgroups: I) lengthening of the residual short bowel to provide satisfactory nutrient amount [48,49], and II) slowing of the intestinal transit [4]. Small bowel transplantation represents a separate option and has been proposed as an alternative for children with permanent intestinal failure and no longer tolerated parenteral nutrition (PN) [11,50].…”
Section: Surgical Techniques To Treat Psbsmentioning
confidence: 99%
See 3 more Smart Citations
“…These procedures pertain to autologous methods of intestinal reconstruction and could be categorized further into two subgroups: I) lengthening of the residual short bowel to provide satisfactory nutrient amount [48,49], and II) slowing of the intestinal transit [4]. Small bowel transplantation represents a separate option and has been proposed as an alternative for children with permanent intestinal failure and no longer tolerated parenteral nutrition (PN) [11,50].…”
Section: Surgical Techniques To Treat Psbsmentioning
confidence: 99%
“…This surgical technique has been used as an adjuvant method in cases of medical management failure. Studies in adults have shown that after interposition, the colon behaves in a similar way to the reversed small intestinal segement [4]. The technique may be performed iso-or antiperistatically [65].…”
Section: Surgical Techniques To Slowing the Intestinal Transitmentioning
confidence: 99%
See 2 more Smart Citations
“…Short bowel syndrome (SBS) is generally defined as a disorder in which the resorptive capacity of the intestine is not sufficient to provide an adequate alimentary supply due to anatomical or functional reasons [1,2]. The incidence of SBS is increasing [3] and varies between 2 and 5 patients per million [1,2,4].…”
Section: Introductionmentioning
confidence: 99%